Growth Performance of Vitex parviflora Juss. and Swietenia macrophylla King in an Abandoned Mining Area at Barangay Maibu, Butuan City, Philippines - Goyo, Shiella Lynn Dali-on; Balgoa, Lovely Carumba; Mantilla, Mirasol Cataluña; Quilicot, Rosemarie Cabal (Jurnal Sylva Lestari, 2025)
This study evaluated the growth performance of V. parviflora and S. macrophylla planted in an abandoned small-scale mining site in Barangay Maibu, Butuan City, Philippines. This study employed a randomized complete block design (RCBD), with growth parameters including height increment, stem diameter increment, and the number of leaves of the seedlings measured over a five-month period. Soil analysis revealed acidic conditions (pH 5.11), low organic matter levels, and nitrogen and phosphorus. Results showed that S. macrophylla exhibited greater height growth (3.96 cm) and stem diameter increase (0.78 cm) compared to V. parviflora (0.72 cm and 0.072 cm, respectively). The number of leaves also increased more in S. macrophylla (10) than in V. parviflora (5). Among the parameters measured, only the height growth showed a statistically significant difference between the two species. In contrast, the differences in stem diameter and number of leaves were not statistically significant. S. macrophylla demonstrated better adaptability and potential for rehabilitating degraded mining sites compared to the other species. However, it is recommended that future studies lengthen the duration to evaluate seasonal fluctuations, long-term growth performance, and possible soil amendment techniques to improve site rehabilitation and forest restoration outcomes. Keywords: abandoned mining site, growth performance, reforestation, Swietenia macrophylla, Vitex parviflora